PENGEMBANGAN MEDIA LAGU SEBAGAI MEDIA PENDUKUNG UNTUK KETERAMPILAN MENYIMAK BAHASA JERMAN PADA KELAS X SMAN 2 SIDOARJO - WAHYU A, RATNA (LATERNE, 2016)
Based on the results of the need analysis, the position of song’s media in SMAN 2 Sidoarjo was very needed in listening Germany learning for students in tenth grade. This purpose of this research is to describe the development process of song’s media and its quality. Used of theory 4D Thiagarajan et al., this is showed that the score that was reached from the validation of questionnare from the media expert were 100%, and score of 94,4% that gotten from the validation of questionnare of the material expert, with the positive responses from the students, 80,37%.   Key words: Development, Song’s Media, Listening